Determinants of Foreign Direct Investment in Bangladesh and India: An Empirical Analysis - Md. Mahbubur, Rahman; Evan, Lau (Research Publishing Academy (RPA), 2018)
This study examines the determinants of foreign direct investment (FDI) in two South Asian neighbouring countries: Bangladesh and India. These two developing countries are trying to attract FDI for accelerating economic growth. However, the inflow of FDI in Bangladesh in comparison with India is very low. Therefore, this paper investigates, analyses, and compares the determinants of FDI between these two economies. Hence, relevant theories and empirical evidence on the determinants of FDI are reviewed first. Next, the research uses secondary data collected from different sources and then employs trend analysis, descriptive statistics, correlation, and regression to examine the variables affecting FDI, such as market size, infrastructure, exchange rate, trade openness, and economic risk. The result from the empirical investigation shows that only the market size of Bangladesh is positive and significant to attract FDI but other independent variables, such as exchange rate, GDP per capita, infrastructure, and trade openness are not significant. On the other hand, GDP per capita, large market size, infrastructure, and exchange rates are positive and significant for India as a recipient of more FDI than Bangladesh. Therefore, the government, policy makers, and business associations of Bangladesh are recommended to focus on developing infrastructure, stabilising macro-economic policy, and reducing the barrier to make the Bangladeshi market more open to the global market so that FDI is encouraged and eventually economic growth. of the country is accelerated